Dihydroartemisinin-sodium taurocholate-PLGA nanoparticles: a novel therapeutic approach against cystic echinococcosis - Moheteer, Aierpati; Zhu, Jiang; Pang, Dongming; Rao, Xue; Aini, Nijiati; Aimulajiang, Kalibixiati; Zhang, Zhenping; Abula, Saifuding; Wusiman, Adelijiang (Frontiers in Pharmacology, 2025)
IntroductionDihydroartemisinin (DHA) demonstrates potent anti-echinococcal activity. However, its clinical application is constrained by non-specific biodistribution and low bioavailability. To overcome these limitations and enhance hepatic targeting, the DHA was encapsulated in poly (lactic-co-glycolic acid) (PLGA) nanoparticles, and using sodium taurocholate (STC) as the surface modifier, a novel composite nanoparticle designated as DHA-STC-PLGA nanoparticles (DSP nanoparticles).MethodsThe formulation was optimized using response surface methodology, and its targeting efficiency was confirmed through in-vivo fluorescence imaging. Both in vitro and in vivo studies were conducted to evaluate the therapeutic efficacy and elucidate the underlying mechanisms of DSP nanoparticles in a murine model of cystic echinococcosis.ResultsThe results showed that the optimal preparation conditions of DSP nanoparticles were 40 mg/mL STC, a DHA/PLGA1:10, ultrasonic power (UP) of 80, and oil in water (O/W) ratio was 1:20. Under these conditions, the DSP nanoparticles size were 125.73 ± 1.78 nm, exhibited a sustained release of DHA, and maintained stability for up to 42 days. DSP nanoparticles demonstrated good safety at a dosage of 200 mg/kg. Additionally, DSP nanoparticles demonstrated effective targeting of the liver and intestines. Therapeutic evaluation in a DSP nanoparticles-treated mouse liver hydatid model revealed that the DSP nanoparticles-H group significantly reduced liver, spleen, and vesicle weights compared to both control and albendazole (ABZ)-treated groups (P <0.05). Furthermore, the DSP nanoparticles-H group significantly decreased serum levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT), total bilirubin (TBIL), direct bilirubin (DBIL), and alkaline phosphatase (ALP). Additionally, levels of interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), and interleukin-10 (IL-10) were significantly reduced in both serum and cystic fluid, while interferon-gamma (IFN-γ) levels were markedly increased (P <0.05). In vitro assays further demonstrated that DSP nanoparticles exert anti-echinococcal effects by compromising the integrity of the cyst wall. Mechanistic results suggest that DSP nanoparticles exert potent anti-echinococcal effects through activation of the Wnt signaling pathway and its key regulatory genes.DiscussionOverall, these findings indicate that DSP nanoparticles represent a promising liver-targeted nanoformulation that not only enhances DHA bioavailability but also offers a potent therapeutic strategy against cystic echinococcosis.